2004
DOI: 10.1104/pp.103.036103
|View full text |Cite
|
Sign up to set email alerts
|

A Dominant Mutation in the Pea PHYA Gene Confers Enhanced Responses to Light and Impairs the Light-Dependent Degradation of Phytochrome A

Abstract: Phytochrome A (phyA) is an important photoreceptor controlling many processes throughout the plant life cycle. It is unique within the phytochrome family for its ability to mediate photomorphogenic responses to continuous far-red light and for the strong photocontrol of its transcript level and protein stability. Here we describe a dominant mutant of garden pea (Pisum sativum) that displays dramatically enhanced responses to light, early photoperiod-independent flowering, and impaired photodestruction of phyA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 67 publications
4
25
0
3
Order By: Relevance
“…More recent studies have identified genes necessary for promotion of flowering under inductive LD photoperiods, including PHYA (Weller et al, 2004) and LATE1, the ortholog of Arabidopsis GI (Hecht et al, 2007), but the primary physiological role and molecular nature of the SN, DNE, and PPD loci have remained unclear. Here, we show that DNE is necessary for the normal rhythmic regulation of circadian clock genes and identify DNE as the pea ortholog of Arabidopsis ELF4.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have identified genes necessary for promotion of flowering under inductive LD photoperiods, including PHYA (Weller et al, 2004) and LATE1, the ortholog of Arabidopsis GI (Hecht et al, 2007), but the primary physiological role and molecular nature of the SN, DNE, and PPD loci have remained unclear. Here, we show that DNE is necessary for the normal rhythmic regulation of circadian clock genes and identify DNE as the pea ortholog of Arabidopsis ELF4.…”
Section: Discussionmentioning
confidence: 99%
“…each photoreceptor, although few data are available to test the conservation of gene function in seed plants other than Arabidopsis. Nonetheless, the available data from Brassica, cucumber (Cucumis sativus), pea (Pisum sativum), tobacco (Nicotiana tabacum), tomato (Solanum lycopersicum), maize (Zea mays), and rice (Oryza sativa) suggest that the functions of phyA and phyB are generally conserved and were established prior to the split of eudicots and monocots (Ballaré et al, 1991;Childs et al, 1991;Devlin et al, 1992;Weller et al, 2004;Sheehan et al, 2007;Takano et al, 2005Takano et al, , 2009, although independently duplicated phyB may subdivide functions differently than is seen in Arabidopsis phyB and phyD (e.g., Hudson et al, 1997;Kerckhoffs et al, 1999;Weller et al, 2000;Sheehan et al, 2007). Functional data from dicots that diverge deeper than the eudicot/monocot split in the angiosperm phylogenetic tree are needed to infer that their functions are conserved in all angiosperms, but this is a reasonable hypothesis.…”
Section: Conservation Of Phya and Phyb Functionmentioning
confidence: 99%
“…Although the majority of phytochrome mutants so far identified have been loss-of-function alleles (for a recent list of phy mutant alleles, see Supplemental Table 2 in ), alleles of phytochromes with increased sensitivity to light and weak constitutive photomorphogenesis (COP) phenotypes have also been reported (Kretsch et al, 2000;Weller et al, 2004;Dieterle et al, 2005;Mateos et al, 2006). The latter are still dependent on light for function, so their functions cannot be analyzed without activating other photobiological processes.…”
Section: Introductionmentioning
confidence: 99%